Evaluation of the Students’s Satisfaction with the Assessment Activities of the National Defense and Security Education Course Results: Case Study at the National Defense and Security Trainning Center, Vietnam National University, Hanoi - Thanh Tung, Tran; Hoang, Le Sy Nguyen (VNU Journal of Science: Education Research; Vol 39 No 1S, 2023)
The research want to evaluate the students’s satisfaction in testing the national defense and security education course results at the VNU National Defense and Security Trainning Center, Vietnam National University, Hanoi. The data was collected from 420 Vietnam Women’s Academy’s students that were studying at the VNU National Defense and Security Trainning Center, Vietnam National University, Hanoi. The result of Cronbach Alpha has shown there are total 5 factors affecting student satisfaction, including: i) Training program; ii) Assessment organization; iii) Teaching staff; iv) Facilities; and v) Test results. In general, students were satisfied with the activities of testing and evaluating the results of defense and security education subjects, in which the teaching staff received the highest satisfaction from students.